2021
DOI: 10.3390/ph14090914
|View full text |Cite
|
Sign up to set email alerts
|

In Silico-Based Design and In Vivo Evaluation of an Anthranilic Acid Derivative as a Multitarget Drug in a Diet-Induced Metabolic Syndrome Model

Abstract: Metabolic syndrome (MetS) is a complex disease that affects almost a quarter of the world’s adult population. In MetS, diabetes, obesity, hyperglycemia, high cholesterol, and high blood pressure are the most common disorders. Polypharmacy is the most used strategy for managing conditions related to MetS, but it has drawbacks such as low medication adherence. Multitarget ligands have been proposed as an interesting approach to developing drugs to treat complex diseases. However, suitable preclinical models that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Multi-target drugs hold promise in addressing intricate conditions such as diabetes, captivating the interest of researchers. Since 2015, the FDA has increasingly approved such drugs, indicating their growing importance in pharmaceutical research [ 51 ]. Bioactive compounds derived from medicinal plants offer a promising option for the management of different ailments with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-target drugs hold promise in addressing intricate conditions such as diabetes, captivating the interest of researchers. Since 2015, the FDA has increasingly approved such drugs, indicating their growing importance in pharmaceutical research [ 51 ]. Bioactive compounds derived from medicinal plants offer a promising option for the management of different ailments with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that levels of oxidative stress markers were decreased by 50 mg/kg MB, and the decrease in oxidative stress markers was maintained up to the 100 mg/kg MB dose [15]. In addition, some polyphenols such as epigallocatechin-3-gallate have been observed to improve insulin resistance by promoting glucose uptake and the antioxidant enzymes superoxide dismutase (SOD) and glutathione peroxidase, attenuating oxidative stress and the inflammatory markers malondialdehyde, tumor necrosis factor 1 alpha (TNF-α), interleukin 6 (IL-6), and nuclear factor kappa beta (NF-κβ) [33].…”
Section: Effect Of Mb Administration On Oxidative Stress Markersmentioning
confidence: 99%
“…However, major problems of this therapeutic method are poor patient compliance, side effects and drug-drug interactions ( Lillich et al, 2021 ). Multi-target ligands and drugs have been proposed as promising approaches to developing therapies for complex diseases ( González-Álvarez et al, 2021 ). Jatrorrhizine is a multi-purpose natural metabolite that affects multiple targets.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%